MENDETEKSI KECURANGAN LAPORAN KEUANGAN: PERSPEKTIF FRAUD DIAMOND MODEL - Juniari, Sang Ayu Putu; Sisdyani, Eka Ardhani (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.01.TAHUN.2024DO - 10.24843/EEB.2024.v13.i01.p14, 2024)
The condition of the company is reflected in the financial statements and management always tries to keep the condition looking good so that it can lead to fraud. One type of fraud is the manipulation of financial statements and the way to detect it is using the fraud diamond model consisting of pressure, opportunity, rationalization, and capability. The purpose of this study was to examine the effect of the elements of the fraud diamond model on the occurrence of financial statement fraud in manufacturing companies listed on the Indonesia Stock Exchange. The sample was determined by purposive sampling observed from 2016-2020, so that 766 observations were obtained. Methods of data collection with documentation techniques. The data analysis technique used is multiple linear regression. The results of the analysis show that pressure has a positive effect on the occurrence of financial statement fraud. Opportunity and rationalization have no effect on the occurrence of fraudulent financial statements. And capability has a negative effect on the occurrence of fraudulent financial statements. Theoretical implications provide implications in the development of fraud detection in financial statements in the perspective of the fraud diamond model.